Explanations for water whitening in secondary dispersion and emulsion polymer films. Issue 16 (19th April 2016) - Liu, Yang; Gajewicz, Agata M.; Rodin, Victor; Soer, Willem‐Jan; Scheerder, Jurgen; Satgurunathan, Guru; McDonald, Peter J.; Keddie, Joseph L.
ABSTRACT: The loss of optical transparency when polymer films are immersed in water, which is called "water whitening, " severely limits their use as clear barrier coatings. It is found that this problem is particularly acute in films deposited from polymers synthesized via emulsion polymerization using surfactants. Water whitening is less severe in secondary dispersion (SD) polymers, which are made by dispersing solution polymers in water without the use of surfactants. NMR relaxometry in combination with optical transmission analysis and electron microscopy reveal that some of the water sorbed in emulsion polymer films is contained within nanosized "pockets" or bubbles that scatter light. In contrast, the water in SD polymer films is mainly confined at particle interfaces, where it scatters light less strongly and its molecular mobility is reduced. The addition of surfactant to a SD creates a periodic structure that displays a stop band in the optical transmission. The total amount of sorbed water is not a good indicator of polymers prone to water whitening. Instead, the particular locations of the water within the film must be considered. Both the amount of water and the size of the local water regions (as are probed by NMR relaxometry) are found to determine water whitening. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1658–1674 Abstract : The loss of optical transparency when polymer films are immersed in water, called "water whitening, " limits their use as clear coatings. This problem is especially acute in films deposited from emulsion polymers, compared with surfactant‐free secondary emulsion polymers. The greatest water whitening occurs when the water is contained in voids, rather than being confined at interfaces between colloidal particles. The total amount of sorbed water is not a good indicator of polymers subject to water whitening.